Cost benefit analysis of lighting retrofit at a house / Muhammad Hasrul Huzairi Ramli - Ramli, Muhammad Hasrul Huzairi (2022)
The potential energy savings, life cycle cost analysis, and payback period of the lighting system at my house is presented in this paper. According to the survey results, fluorescent lamps account for 100% of the lighting system at my house. In terms of prospective energy savings, life cycle cost analysis, and payback duration, a cost benefit study of retrofitting with more efficient lighting systems was undertaken. On the basis of energy usage, a comparison of existing and retrofitting lighting systems is offered. Based on the findings, it can be inferred that using energy efficient lighting systems will save large amounts of energy and money while also lowering emissions indirectly.